2019
DOI: 10.11604/pamj.2019.33.168.12733
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and utilization of female condoms among street youths in Ibadan, an urban setting in South-West Nigeria

Abstract: IntroductionFemale condom awareness and use have been poorly documented in sub-Saharan region especially among street youths. This study assessed its awareness and use among street youths.MethodsA cross-sectional study was conducted among 964 youths between ages 15 to 24 years old using questionnaires to elicit information. Univariate and multivariate analysis were conducted at 5% level of significance.ResultsMore than half (69.9%) were males and between 20-25 years of age (61.2%). More than three-quarter (81.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
(26 reference statements)
3
4
0
Order By: Relevance
“…2b ). Use was similar in both studies that interviewed male respondents, which reported use of 5.5% and 4.6%, respectively 14 , 17 . Of the fifteen studies that reported the use of the FC, the 2007 National HIV/AIDS and Reproductive Health Survey (NARHS) reported the lowest use of the FC (0.4%) 2 9 .…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…2b ). Use was similar in both studies that interviewed male respondents, which reported use of 5.5% and 4.6%, respectively 14 , 17 . Of the fifteen studies that reported the use of the FC, the 2007 National HIV/AIDS and Reproductive Health Survey (NARHS) reported the lowest use of the FC (0.4%) 2 9 .…”
Section: Resultssupporting
confidence: 59%
“…2b). Use was similar in both studies that interviewed male respondents, which reported use of 5.5% and 4.6%, respectively 14,17 .…”
Section: Participants and Statistical Analysissupporting
confidence: 59%
See 3 more Smart Citations